Answer:
![\displaystyle f(x) = -(x-4)^2 + 6](https://img.qammunity.org/2022/formulas/mathematics/high-school/80lwexacwyia8oo6nyvltummue5d4kzr5m.png)
Explanation:
A given quadratic has its vertex at (4, 6) and the point (1, -3). We want to write the equation in vertex form of the quadratic.
Recall that vertex form is given by:
![\displaystyle f(x) = a(x-h) ^2 + k](https://img.qammunity.org/2022/formulas/mathematics/high-school/wg4airuxf0e8wvo9isixb8b06k8jfa1wp8.png)
Where (h, k) is the vertex and a is the leading coefficient.
Since our vertex is at (4, 6), h = 4 and k = 6:
![\displaystyle f(x) = a(x - 4)^2 + 6](https://img.qammunity.org/2022/formulas/mathematics/high-school/xu79e1i7i5x6bf0sk3dwocnm9yq4b21aye.png)
To determine the leading coefficient, since we are given that (1, -3) is a point on the parabola, when x = 1, y = -3. Substitute and solve for a:
![\displaystyle \begin{aligned} (-3) & = a((1)-4)^2 + 6 \\ \\ -3 & = a(-3)^2 + 6 \\ \\ 9a & = -9 \\ \\ a & = -1 \end{aligned}](https://img.qammunity.org/2022/formulas/mathematics/high-school/tg6s3843hf56gay3jbboz6jakc8u2gndyg.png)
Hence, the leading coefficient a is -1.
Then our equation in vertex form is:
![\displaystyle f(x) = -(x-4)^2 + 6](https://img.qammunity.org/2022/formulas/mathematics/high-school/80lwexacwyia8oo6nyvltummue5d4kzr5m.png)